Results from Bottom Trawl Survey on Flemish Cap of July 2011 - Vázquez, Antonio (Northwest Atlantic Fisheries Organization, 2012)
44 páginas, 14 figuras, 32 tablas.-- Scientific Council Meeting A stratified random bottom trawl survey on Flemish Cap was carried out on July - August 2011, covering the bank up to 1460 m depth (800 fathoms). The survey was carried out on board R/V Vizconde de Eza, using a Lofoten bottom trawl gear, and 128 haul were done, 79 of them in the region with less than 730 m depth. Survey results are presented and compared with results of previous surveys in the series since 1988. Biomass and abundance indices are provided for main commercial species, as well as age composition for cod, American plaice, Greenland halibut, and roughhead grenadier. This study was supported by the European Commission (Program for the Collection of Data in Fisheries Sector), IEO and CSIC. Peer reviewed